Properties of chlorophyll based organic dye sensitizer molecule extracted in various solvents / Azlina Ahmad Khan ...[et al.] - Ahmad Khan, Azlina; Zainal, Nurfarahin; Mokhtar, Marina; Mamat, Mohamad Hafiz; Abdullah, Mohd Hanapiah (UiTM Press, 2022)
Dye-sensitized solar cell (DSSC) has been actively researched due to its lower fabrication cost. In DSSC, sensitizer imitates photosynthesis process in plants by absorbing the photon energy from the sunlight. This research investigated methanolic extracted chlorophyll dye sensitizer in comparison to water extracted and bare chlorophyll. Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TD-DFT) methods in Gaussian 03/Gaussview 03 software were used to investigate its optical and electronic properties. Each of the molecular structure (methanol and water) was individually attached to chlorophyll, and their performances were determined. Results demonstrated that the absorbance spectrum of chlorophyll shows a broad peak in the visible range from 400 to 700 nm with its highest peak at 430 nm. Energy gap of chll-m between the E(LUMO) and the conduction band of TiO2 semiconductor, EC(TiO2) or so called as VOC is slightly smaller compared to water (chll-w). Meanwhile, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) bandgap of chll-m is slightly higher at 2.13 eV. Finally, position of LUMO to redox electrolyte in chll-m is the lowest, which is favourable for faster electron transition. From observation, chll-m demonstrated better optical and electronic properties compared to its counterparts and hence good for chlorophyll sensitizer extraction.